2022
DOI: 10.1103/physrevb.105.174437
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular and square skyrmion crystals on a centrosymmetric square lattice with easy-axis anisotropy

Abstract: We investigate the instability toward a skyrmion crystal under an in-plane magnetic field in centrosymmetric tetragonal magnets. By performing the simulated annealing for a spin model on the square lattice, we find that the interplay among the easy-plane two-spin anisotropic interaction, positive biquadratic interaction, and high-harmonic wave-vector interaction plays an important role in stabilizing the skyrmion crystal in the in-plane external magnetic field. The obtained skyrmion crystal consists of a pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 96 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…that the effect of magnetic frustration in momentum space is large, which becomes the origin of two types of the SkXs (S-SkX and R-SkX) [59,60]. Indeed, for this set of model parameters, it was revealed that the above two SkXs appear in the presence of an external magnetic field H in the second term in equation ( 1) [52].…”
Section: Model and Methodsmentioning
confidence: 86%
“…that the effect of magnetic frustration in momentum space is large, which becomes the origin of two types of the SkXs (S-SkX and R-SkX) [59,60]. Indeed, for this set of model parameters, it was revealed that the above two SkXs appear in the presence of an external magnetic field H in the second term in equation ( 1) [52].…”
Section: Model and Methodsmentioning
confidence: 86%
“…This is just the tip of the iceberg of topological non-trivial spin textures [39]. On the one hand, it has been proved that the skyrmion can also appear in the centrosymmetric magnets as a result of other interactions [49][50][51][52][53][54][55][56][57][58][59][60], such as dipolar interaction [49,50], the single-ion anisotropy [51][52][53][54][55][56][57][58] or the bond-dependent interactions [54,61]. On the other hand, beyond the skyrmion, there are many magnetic quasi-particles coming into the sight of researchers in recent years [39,62,63].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the stabilization of the centrosymmetric square SkX has been achieved by considering the further effect of the bonddependent anisotropic exchange interaction or the dipolar interaction in addition to the frustrated exchange interaction in insulating magnets [89,90] and the multiple-spin interaction in magnetic metals [87,[146][147][148][149], which reproduces the multiple-Q instabilities observed in GdRu 2 Si 2 [103][104][105]. Besides, the scenario based on the competing interactions in momentum space has recently been proposed, which might explain the multiple SkX phases including the square SkX in EuAl 4 [109,150,151].…”
Section: Introductionmentioning
confidence: 99%